Positioning a navigation-guided cephalic screw standard gamma 3 nail in intertrochanteric fractures: preliminary experience - Lana, Debora; Mobilia, Giuseppe; Ortolani, Alessandro; Stallone, Stefano; Comitini, Saverio; Tigani, Domenico (Lo Scalpello - Journal, 2021)
Objective. Hip fractures in elderly people occur in up to 18% of women and 6% of men, with almost 50% located at lateral proximal femur. Surgical treatment prevents complications secondary to immobilization. Intramedullary fixation has the advantages of reduced blood loss and shorter surgical time. The rate of complications rate is around 20%, represented by screw jamming, refractures, implant breakage, or its medial migration, although the most common is cut-out. As a general consensus, a tip-apex-distance (TAD) of > 25 mm and incorrect cephalic screw position are predictive factors of cut-out. Methods. The aim of this study is to evaluate the incidence of cut-out in patients treated with intramedullary nail fixation associated with a computer-guided system to place the cephalic screw. We present a small case series of 10 patients. Results. Interventions were performed heterogeneously by different surgeons. Mean TAD was 13.3 mm. Positioning resulted on average 2 mm lower and 1 mm anterior than planned by the system. At a mean follow-up time of 6.5 months, there were no cut-outs. Conclusions. Further studies with longer follow-up are needed, but preliminary results showed that a navigation system for cephalic screw positioning can be helpful in intramedullary fixation of proximal lateral femur fractures to prevent cut-out.